A comparative analysis of interobserver reliability and intraobserver reproducibility of the Oswestry-Bristol Classification and the Dejour Classification for trochlear dysplasia of the knee - Kunal D. Roy; Pushkar Joshi; Ibrahim Ali; Pritom M. Shenoy; Ibrahim Malek; David Barlow; Asad Syed; Yogesh Joshi (Bone & Joint Open, 2023)
Aims: Classifying trochlear dysplasia (TD) is useful to determine the treatment options for patients suffering from patellofemoral instability (PFI). There is no consensus on which classification system is more reliable and reproducible for the purpose of guiding clinicians’ management of PFI. There are also concerns about the validity of the Dejour Classification (DJC), which is the most widely used classification for TD, having only a fair reliability score. The Oswestry-Bristol Classification (OBC) is a recently proposed system of classification of TD, and the authors report a fair-to-good interobserver agreement and good-to-excellent intraobserver agreement in the assessment of TD. The aim of this study was to compare the reliability and reproducibility of these two classifications. Methods: In all, six assessors (four consultants and two registrars) independently evaluated 100 axial MRIs of the patellofemoral joint (PFJ) for TD and classified them according to OBC and DJC. These assessments were again repeated by all raters after four weeks. The inter- and intraobserver reliability scores were calculated using Cohen’s kappa and Cronbach’s α. Results: Both classifications showed good to excellent interobserver reliability with high α scores. The OBC classification showed a substantial intraobserver agreement (mean kappa 0.628; p < 0.005) whereas the DJC showed a moderate agreement (mean kappa 0.572; p < 0.005). There was no significant difference in the kappa values when comparing the assessments by consultants with those by registrars, in either classification system. Conclusion: This large study from a non-founding institute shows both classification systems to be reliable for classifying TD based on axial MRIs of the PFJ, with the simple-to-use OBC having a higher intraobserver reliability score than that of the DJC. Cite this article: Bone Jt Open 2023;4(7):532–538.